2006
DOI: 10.1177/1043659605281982
|View full text |Cite
|
Sign up to set email alerts
|

Healing Fractured Families: Parents’ and Elders’ Perspectives on the Impact of Colonization and Youth Suicide Prevention in a Pacific Northwest American Indian Tribe

Abstract: Suicide rates among American Indian youth in the United States are two to three times the national average. Risk factors for American Indian youth include depression, alcohol use, hopelessness and stress, and family conflict, abuse, poverty, and instability. In this descriptive study, the authors aimed to obtain parents' and elders' perspectives on community needs and to identify strengths on which the community might build to reduce youth suicide risk. Data were collected from focus groups with 40 American In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…For instance, one tribal-specific prevention intervention includes culturally specific assessment, recognizes historical and cultural contextual factors, and allows for traditional healing approaches (Fisher & Ball 2002). Healing intergenerational pain is perceived as one way to prevent suicide (Strickland, Walsh & Cooper 2006) and one small qualitative study explored perceptions of effective traditional healing components among Indigenous Peoples in Canada (McCabe 2007). These studies point to the importance of incorporating HT and HTR into treatment and prevention interventions.…”
Section: The Historical Trauma and Unresolved Grief Interventionmentioning
confidence: 99%
“…For instance, one tribal-specific prevention intervention includes culturally specific assessment, recognizes historical and cultural contextual factors, and allows for traditional healing approaches (Fisher & Ball 2002). Healing intergenerational pain is perceived as one way to prevent suicide (Strickland, Walsh & Cooper 2006) and one small qualitative study explored perceptions of effective traditional healing components among Indigenous Peoples in Canada (McCabe 2007). These studies point to the importance of incorporating HT and HTR into treatment and prevention interventions.…”
Section: The Historical Trauma and Unresolved Grief Interventionmentioning
confidence: 99%
“…Despite the long held belief by researchers and indigenous peoples alike of the positive relationship between traditional culture and mental well-being (Johnson & Tomren, 1999;Kirmayer et al, 2000;Strickland, Walsh, & Cooper, 2006;Wexler & Goodwin, 2006;Wolsko, Lardon, Hopkins, & Ruppert, 2006), the topic has not been extensively studied quantitatively. With regard to suicide, Chandler and colleagues have found that those FN communities in B.C.…”
Section: Substance Usementioning
confidence: 99%
“…The report by the Royal Commission on Aboriginal People (Government of Canada, 1996) describes how Indigenous people are going through a loss of cultural identity, high rates of poverty, limited employment opportunities, inadequate living conditions, weakened social structures, and ongoing racism. For many Indigenous employees, these demoralizing conditions have contributed to increased substance abuse, suicide, violence, and mortality (Chandler & Lalonde, 1998;Freeman, 2004;Olson & Wahab, 2006;Strickland, Walsh, & Cooper, 2006;White Bear, 2003;).…”
Section: Health Sovereignty Through Eapmentioning
confidence: 97%